Viscosity, surface tension and refractive index of tetraethylorthosilicate-based sol-gel materials depending on ethanol content - Hołowacz, Iwona; Podbielska, Halina; Bauer, Joanna; Ulatowska-Jarża, Agnieszka (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The sol-gel-derived materials can be exploited for the number of applications, including biomaterials and measuring techniques. One of the most important applications involves production of sol-gel coatings. In this study, silica based sol-gel materials were prepared by way of acid hydrolysis with alcohol as a solvent. Tetraethylorthosilicate (TEOS) was used as a precursor. Different samples were tested; with molar ratios R = 5, 10, 15, 20, 32 and 50, denoting the number of ethanol moles to the number of TEOS moles. The viscosity and surface tension of liquid hydrolizates were measured depending on the ethanol content in sol-gel. The thickness of a coating layer was determined, as well. The refractive index was measured 10 days long, up to the point of gelation. It was demonstrated that viscosity, surface tension and refractive index are lower for higher R value (for higher alcohol content), whereas the sol-gel layers produced with higher R values are thicker than these ones produced with lower alcohol content. It is also demonstrated that R value influences the performance of fiberoptic sol-gel applicators for interstitial laser therapy.
Optica Applicata, Vol. 35, 2005, nr 4, s. 691-699
Keywords: optyka; sol-gel coating; sol; viscosity; surface tension; refractive index